PRACTICE-ORIENTED APPROACH TO THE FORMATION OF EDUCATIONAL PROGRAMS AT THE TRANSITION TO THE SYSTEM OF ADVANCED TRAINING - O. E. Astafyeva (Вестник университета)
The possibility of applying a new form of personnel training on the principle of an open system that includes training modules that are embedded in the educational program based on «best practices» has been analysed. When implementing the educational program, the circle of participants has been expanded. The participants are partner universities and enterprises that provide access to new technologies and material and technical base. The proposed practice-oriented model of education allows us to form a rational mechanism for co-financing educational programs by all its participants. An approach to personnel training with a reserve of high professional growth based on a practice-oriented educational environment has been proposed. The conducted analysis of normative legal acts has made it possible to determine the most effective forms of interaction between participants in the educational platform and new principles for organizing advanced training. The role of innovative scientific and technological centers in the formation of a new model of personnel training has been determined.